Polyphase Glacigenic Deformation of Advance Glaciofluvial Sediments, Near Big Creek, British Colombia - Huntley, David; Broster, Bruce (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1993)
ABSTRACTDeformation structures were observed in glaciofluvial sediments near Big Creek, central British Columbia. These sediments record a sequence of polyphase deformation resulting from the advance and retreat of the Late Wisconsinan (Fraser Glaciation) Cordilleran Ice Sheet. Deformation is attributed to ductile then brittle failure resulting from: (a) horizontal compression and loading as ice advanced over saturated sediments; followed by (b) lateral extension then (c) compression under frozen conditions during glacier overriding; and finally (d) vertical extension during unloading upon déglaciation. Most deformation (a-c, above) appears to have occurred during the advance phase of the Fraser Glaciation.